MURAL, KEKUATAN MODAL, DAN MASYARAKAT - Akbar Annasher (DeKaVe, 2011)
Broadly speaking, this paper discusses the phenomenon of murals that are now spread in Yogyakarta Special Region, especially the city of Yogyakarta. Mural painting is an art with a media wall that has the elements of communication, so the mural is also referred to as the art of visual communication. Media is a media wall closest to the community, because the distance between the media with the audience is not limited by anything, direct and open, so the mural is often used as media to convey ideas, the idea of ??community, also called the media the voice of the people. Location of mural art in situations of public spatial proved inviting the owners of capital to use such means, in this case is the mural. Manufacturers of various products began racing the race to put on this wall media, as time goes by without realizing the essence of the actual mural art was forced to turn to the commercial essence, the only benefit some parties only, the power of public spaces gradually occupied by the owners of capital, they hopes that the community can view the contents of messages and can obtain information for the products offered. it brings motivation and cognitive and affective simultaneously in the community.Keywords: Mural, Public Space, and Society.